The case of the disappearing whistleblower: an analysis of National Health Service inquiries. Issue 2 (17th February 2022) - Powell, Martin; Blenkinsopp, John; Davies, Huw; Mannion, Russell; Millar, Ross; McHale, Jean; Snowden, Nicholas
IMPACT: Despite the recognition that 'speaking up' or 'whistleblowing' can make a major contribution to the quality and safety of health services, many inquiries into poor care did not appear to blow the whistle loudly enough and governments failed to listen and act appropriately when they did. Policy-makers and practitioners need to consider the importance of whistleblowing; if existing policies are working, or new ones need to be introduced, and—if so—whether they should be based on cultural or legal remedies. In particular, as many international organizations and nations have focused on whistleblowing in recent years, policy-makers in the UK should review whether legislation is required to update or replace its existing whistleblowing law.